Peran Kepemimpinan Sekolah dalam Meningkatkan Kualitas Pendidikan Anak Usia Dini - Nuraida Hartati; Rabi’ah Adawiyah; Rahmayanti Eka Putri; Sofia Rakhmalina; Aslamiah Aslamiah; Celia Cinantya (Jurnal Pendidikan Anak Usia Dini dan Kewarganegaraan, 2025)
Early Childhood Education (ECE) is a very important foundation or starting point for building physical, mental, and social development in children so that they have the preparation that can help them later when they grow up. Therefore, an educational institution must have a leader or principal who can provide motivation and good and adequate facilities for the teachers and students. A quality leader is also very important so that students not only gain knowledge and science, but they can also form their own character with moral values as preparation when they grow up. We examine a variety of publications in this essay using a qualitative approach. We obtained knowledge from several sources, including publications connected to our topic and academic magazines. The results of this study illustrate that the presence of quality leadership in an educational institution, particularly in early childhood education (ECE), can optimize and develop the potential of teachers, making them more improved and creative, and can also shape the character of the students.